Digit Sucking Habit And Association With Dental Caries And Oral Hygiene Status In Children - HARIKRISHNAN, RESHMA; RAMAKRISHNAN, MAHESH; GANESH S, BALAJI (The journal of contemporary issues in business and government, 2021)
A habit is a routine of behavior or doing that is repeated regularly and tends to occur unconsciously. Oral habits such as thumb sucking, nail and finger biting, tongue thrusting, lip biting , bruxism, etc can produce deleterious and destructive effects on the oral structures. A patient's oral health can be affected by these adverse habits. Thumb/digit sucking habit is the repeated and forceful sucking of the thumb with associated buccal and lip musculature. Dental caries is a common problem to any dentition, at any age group. They are most prevalent in cases with poor oral hygiene maintenance. The aim of this study is to assess the association between oral hygiene and DMFT index with dental caries, in children with digit sucking habits. A retrospective study was done in an institutional setting to study the relation between oral hygiene status and dental caries in patients with digit sucking habits. All patients (age group of 18 and less) who had visited the hospital from June 2019 to April 2020 were taken into consideration. The case sheets of all the patients were analyzed using the parameters such as gender, OHIS, DMFT. The data was tabulated and statistical analysis was done in SPSS. Analysis of gender with DMFT and OHIS were done. Out of the 18 patients with digit sucking habits, 11 of them were male and 7 of them were females. Majority of the patients had a really low score on the DMFT index. 0-5 was the lowest and 15 patients had this score. 8 patients had OHIS between 0.6-1. Male patients were seen to have higher DMFT and OHIS than female patients. There was no significant relation between digit sucking habit and dental caries. Oral hygiene played a big role in the occurrence of dental caries.